PRODUCTION MANAGEMENT OF BROILER PARENT STOCK IN PT. JAPFA COMFEED INDONESIA Tbk. POULTRY BREEDING DIVISION PUPUAN 1 - N. M. A. K., Dewi; Dewantari, M.; Suarta, I G. (Jurnal Peternakan Tropika; Vol 6 No 1 (2018): Vol. 6 No. 1 (2018), 2018)
This study aims to know about production management of broiler parent stock in PT Japfa Comfeed Indonesia Tbk. Poultry Breeding Division Pupuan 1, village Batungsel, district Pupuan, Tabanan Regency, Bali Province has been executed for 3 weeks, starting from 16 October-4 November 2017.  The data collected in this study consisted of primary data obtained by direct survey, interview and observation techniques, and secondary data obtained through notes or reports from other reliable sources.  The variables observed in this study are the general description of the company; maintenance management of broiler parent stock consisting of sanitation, feed, drinking water, litter, lighting, ventilation, and density; as well as the percentage of egg production and hatching egg.  The results showed that the management of broiler parent stock production in PT. Japfa Comfeed Indonesia Tbk. Poultry Breeding Division Pupuan 1 consisting of sanitation, feeding, drinking, litter, lighting, ventilation and density is done well based on the standard operational procedure as well as able to hiigh produce of the percentage egg production and hatching egg.  PT. Japfa Comfeed Indonesia Tbk. Poultry Breeding Division Pupuan 1 is performed well, shown by a high production quantity followed by the percentage of hatching egg produced. Keywords: broilerparent stock, production management, production